2011
DOI: 10.1080/09540251003674113
|View full text |Cite
|
Sign up to set email alerts
|

Changing times of feminism and higher education: from community to employability

Abstract: This article discusses the creation of space and time for feminist approaches in higher education in the context of shifting community and employment relations and the restructuring of higher education space-time. It draws on the reflections of three feminist academics concerning aspects of their work biographies in two very different higher education settings. It explores the shift from working in an academic department concerned with community studies to one concerned with education and related employment. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…With the development and use of new technological devices and the Internet (Torkzadeh and Van Dyke, 2002; Weatherbee, 2010) together with the economic crisis (Utting et al, 2012) and the different types of social interaction (Tyler, 2002), modern society has been defined as an information society (Webster, 2002), a knowledge society (Hargreaves, 2003), and even a liquid society (Bauman, 2000, 2011). The pace and expansion of markets, globalization, the effect of new technologies, and high-performance competition scenarios are key developments in today's society (Moss and Richter, 2011; Pavlin and Svetlicic, 2012; Minten and Forsyth, 2014; Casano, 2015; Kalfa and Taksa, 2015). …”
Section: Discussionmentioning
confidence: 99%
“…With the development and use of new technological devices and the Internet (Torkzadeh and Van Dyke, 2002; Weatherbee, 2010) together with the economic crisis (Utting et al, 2012) and the different types of social interaction (Tyler, 2002), modern society has been defined as an information society (Webster, 2002), a knowledge society (Hargreaves, 2003), and even a liquid society (Bauman, 2000, 2011). The pace and expansion of markets, globalization, the effect of new technologies, and high-performance competition scenarios are key developments in today's society (Moss and Richter, 2011; Pavlin and Svetlicic, 2012; Minten and Forsyth, 2014; Casano, 2015; Kalfa and Taksa, 2015). …”
Section: Discussionmentioning
confidence: 99%
“…Feminist academics may be particularly vulnerable due to shifts in the relationships between staff and students (Lee, 2005) and desires to maintain high levels of student support despite increasing target-driven managerialism (Moss & Pryke, 2007). Within this changing context, existing gendered working practices and relations continue to be reproduced with pressures to recruit more students to courses reducing time for all academics, including feminist academics, to work with students to challenge these gendered norms (Moss & Richter, 2011).…”
Section: Feminist Academicsmentioning
confidence: 99%
“…As Lee (2005) has suggested, there are increasing tensions between staff and the student body. This is in the context of increased focus on graduate employability, even within feminist academic contexts (Moss and Richter, 2011). The data presented here suggests some students share these concerns and question the relevance of feminism and feminist perspectives to their employability within the business world.…”
Section: Discussionmentioning
confidence: 77%
“…Moss and Pryke (2007) have suggested that feminist academics may feel greater pressure than other academics to maintain high levels of student support, for example, pastoral care, while attempting to achieve excellent research. Moss and Richter (2011) have suggested that changes to university funding and the pressure to increase student numbers may reduce the scopeacademics have for working with students to challenge gendered norms.…”
Section: Feminist Academicsmentioning
confidence: 99%